Functional effects of treadmill-based gait training at faster speeds in stroke survivors: a prospective, single-group study. Issue 3 (September 2017) - Mohammadi, Roghayeh; Ershad, Navid; Rezayinejad, Marziyeh; Fatemi, Elham; Phadke, Chetan P.
Abstract : To examine the functional effects of walking retraining at faster than self-selected speed (SSS). Ten individuals with chronic stroke participated in a 4-week training over a treadmill at walking speeds 40% faster than SSS, three times per week, 30 min/session. Outcome measures assessed before, after, and 2 months after the end of intervention were the Timed Up and Go, the 6-Minute Walk, the 10-Meter Walk test, the Modified Ashworth Scale, SSS, and fastest comfortable speed. After 4 weeks of training, all outcome measures showed clinically meaningful and statistically significant improvements ( P <0.05) that were maintained at 2 months after the end of the training. The results showed that a strategy of training at a speed 40% faster than SSS can improve functional activity in individuals with chronic stroke, with effects lasting up to 2 months after the intervention.